Comparison of the Initiation Time of Enteral Nutrition for Critically Ill Patients: At Admission vs. 24 to 48 Hours after Admission. (18th September 2021) - Yu, Anshan; Xie, Yanmei; Zhong, Meixin; Wang, Fen; Huang, Huachun; Nie, Liang; Liu, Xiaofeng; Xiao, Mingfang; Zhu, Hongquan
Abstract : Objective . To investigate the better time of initiation of enteral nutrition for critically ill patients, such as at admission or 24 to 48 hours after admission. Methods . This was a prospective, randomized, parallel-controlled, single-blind, interventional clinical trial. A total of 100 patients admitted to the intensive care unit (ICU) of our hospital between January 2017 and December 2018 were recruited in this study. These patients had been divided into the control group or intervention group by a computer-generated random number table, and each group had 50 patients. For the control group, a gastric tube was inserted to start enteral nutrition at 24 to 48 hours after admission. For the intervention group, a nasojejunal tube was placed to start enteral nutrition at admission. The main endpoints included serum albumin and prealbumin at admission and on days 3, 7, and 14 after admission, length of ICU stay, ventilator time, and complications such as diarrhea, gastric retention, esophageal reflux, and pulmonary infection. Results . The results showed that serum albumin and prealbumin were significantly higher in the intervention group than in the control group (P < 0.05). The length of ICU stay (P < 0.05) and ventilator time (P < 0.05) were both significantly shorter in the intervention group than in the control group. The incidences of gastric retention, esophageal reflux, and pulmonary infection were significantly lower in the intervention group than those in the control group (P < 0.05). Conclusion . In the absence of contraindications, enteral nutrition can be initiated immediately after admission to the ICU (within 6 hours), and feeding nasojejunal tube is recommended. It can improve the nutritional status and prognosis of critical patients, improve the feeding effect, shorten the length of stay in the ICU and the use of the ventilator, and reduce the incidence of complications.